Comparison of blood glucose levels in breastfed vs. formula-fed low birth weight infants - Eli Tua Pangaribuan; Bugis M. Lubis; Pertin Sianturi; Emil Azlin; Guslihan D. Tjipta (Indonesian Pediatric Society Publishing House, 2009)
Background  Low  birth weight infants are defined  as  babies with birth weight less  than  2500 grams.  Low  birth weight infants tend to suffer from hypoglycemia compared to full term infants.  The incidence  of  hypoglycemia in newborns varies between 1.3 and  3 per 1000 live births. Blood glucose levels in formula-fed infants are lower  than  those in breastfed infants. Objective  To  compare blood glucose levels in breastfed  and formula-fed low birth weight infants. Methods  A cross sectional study was conducted between February 2007  and  June 2007  at  Pirngadi and H. Adam Malik General Hospital in Medan,  North  Sumatra, Indonesia. All low birth weight babies were classified into two groups: the breastfed  and formula-fed. Each group consisted  of  32 infants. Capillary blood was collected using heel pricks  at  1,  48,  and  72 hours after birth, and plasma glucose was evaluated using the Glucotrend2 blood glucose test. Results  The  breastfed low birth weight infants had significantly higher blood glucose levels (P=0.002)  than  formula-fed low birth weight infants. Mode of delivery  was  related to blood glucose level. Infant delivered  by  caesarean section had significantly different blood glucose levels  at  1 hour  (P=0.005)  and  72  hours after birth (P=0.027).  The  full-term infants had significantly higher blood glucose level (P=0.007)  than  the small for gestational age infants. Conclusions  Generally,  low  birth weight infants have hypoglycemia after first hour  of  delivery. Breastfed low birth weight infants have higher blood glucose levels  than  formula-fed low birth weight infants.